2010
DOI: 10.4161/epi.5.3.11409
|View full text |Cite
|
Sign up to set email alerts
|

5-azacytidine treatment reorganizes genomic histone modification patterns

Abstract: Methylation of DNA in combination with histone modifications establishes an epigenetic code that ensures the proper control of gene expression. Although DNA methyltransferases have been shown to interact with histone methyltransferases such as EZH2 (which methylates histone H3 on lysine 27) and G9a (which methylates histone H3 on lysine 9), the relationship between DNA methylation and repressive histone marks has not been fully studied. In cancer cells, promoters of genes are often aberrantly methylated. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 33 publications
7
104
2
1
Order By: Relevance
“…41 We initially determined two sublethal concentrations of AZA (1 and 5 mM, freshly prepared every time) and used them as reported elsewhere. 34 Experimental design of AZA in vitro treatment was described previously 40 and consists of three doses of 1 or 5 mM AZA every 24 h and alternatively three doses of G-CSF 50 ng/ml (Neupogen, Amgen, Thousand Oaks, CA, USA) or granulocyte --macrophage (GM)-CSF 50 ng/ml or macrophage (M)-CSF 50 ng/ml (Sigma-Aldrich, St Louis, MO, USA, GM-CSF---cat. no.…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…41 We initially determined two sublethal concentrations of AZA (1 and 5 mM, freshly prepared every time) and used them as reported elsewhere. 34 Experimental design of AZA in vitro treatment was described previously 40 and consists of three doses of 1 or 5 mM AZA every 24 h and alternatively three doses of G-CSF 50 ng/ml (Neupogen, Amgen, Thousand Oaks, CA, USA) or granulocyte --macrophage (GM)-CSF 50 ng/ml or macrophage (M)-CSF 50 ng/ml (Sigma-Aldrich, St Louis, MO, USA, GM-CSF---cat. no.…”
Section: Cell Linesmentioning
confidence: 99%
“…AZA affects DNA methylation status of the derepressed genes 34 and may also involve histone modifications. 35 --38 Epigenetic therapies may not simply block the tumor cell growth 39 but induce cellular differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…To account for differences in initial methylation at each CpG site and amount of methylation lost, we normalized CpGs by their initial and post-treatment DNA methylation levels, such that the degree of demethylation achieved after 6 d of treatment was 100%. DNA methylation changes at later time points (3,6,9, and 27 passages) were used to calculate the fractional recovery of methylation over time in the absence of drug. A self-organizing map (SOM) 21 approach was then used to cluster the CpGs into classes based on their patterns of remethylation.…”
Section: Kinetics Of Cpg Remethylation Following Dac Withdrawalmentioning
confidence: 99%
“…Although tumor-suppressor genes are frequently silenced in cancer through hypermethylation of promoter-associated CpG Islands (CGI), 8 and DAC is capable of reversing this aberrant methylation to achieve gene reactivation, less than 10% of DACinduced transcriptional changes are accounted for by relief of promoter hypermethylation. 9,10 Cell culture studies have demonstrated that at low doses, transient exposure to DAC results in a loss of tumorigenic potential that persists for many generations following drug withdrawal, 11 suggesting that durable methylation changes underlie its antitumor activity. Leukemia cells from patients undergoing DAC treatment experience rapid remethylation at the end of each treatment cycle, as measured globally, 12 and at LINE elements.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, 5-azacytidine reduces DNA methylation by inhibiting the methyl transferase DNMT1, but has additional effects on chromatin and gene regulation [8]. To further test the hypothesis that increased Clinically, high levels of 2HG may sensitise IDH-mutant tumour cells to other therapeutic approaches [1].…”
mentioning
confidence: 99%